CULTURAL AND GENDERED OPPRESSION IN AMERICAN AND UZBEK WOMEN’S LITERATURE - Shoymardonova Gulandom Elbek kizi (Bright Mind Publishing, 2025)
This study investigates the manifestation of gendered and cultural oppression in American and Uzbek women’s literature, focusing on The Awakening (Chopin), The Bell Jar (Plath), and selected Uzbek works. Applying feminist and discourse-analytic frameworks—including gynocriticism and critical discourse analysis—it demonstrates how linguistic choices, narrative tropes, and cultural tropes both constrain and empower female protagonists across contexts. Findings reveal shared themes of internal exile, resistance through symbol and speech, and the critical role of language in articulating liberation. The Uzbek context enriches American-centric discourse by emphasizing tradition, translation, and cultural specificity.
Keywords: Gendered, oppression, cultural, context, feminist, discourse analysis, American literature, Uzbek, women’s writing, translation, gynocriticism.